Conventional radiography and correlated factors of enthesopathies of the Achilles tendon and plantar fascia in patients with axial spondyloarthritis - E. Yılmaz; Ö. Pasin (PAGEPress Publications, 2024)
Objective. This study aimed to investigate the correlated risk factors and presence of radiological enthesopathies of the Achilles tendon and plantar fascia in patients with axial spondyloarthropathy (axSpA). Methods. 242 patients (121 female and 121 male) with axSpA were included in this study. The Bath Ankylosing Spondylitis Disease Activity Index (BASDAI), the Bath Ankylosing Spondylitis Functional Index (BASFI), the Ankylosing Spondylitis Disease Activity Score with C-reactive protein (ASDAS-CRP), the Bath Ankylosing Spondylitis Radiology Index (BASRI), the Maastricht Ankylosing Spondylitis Enthesitis Score (MASES), and CRP were evaluated in all patients. The lateral foot X-rays of the patients were assessed for enthesopathies of the Achilles tendon and plantar fascia attachments. Results. Calcaneal spur and Achilles enthesopathies were present in 57.4% of the patients. 39.3% of patients had enthesopathies in both regions. The male and female groups differed statistically in terms of weight, height, body mass index (BMI), positive family history, and duration since diagnosis (p<0.05). The presence of calcaneal spur and Achilles enthesopathies was found to be significantly correlated with age, weight, BMI, symptom duration, and the score of BASDAI, BASFI, ASDAS-CRP, BASRI, and MASES (p<0.05). Conclusions. The presence of enthesopathies appears to be associated with age, weight, BMI, symptom duration, and disease activity. Conventional radiography can be used as an auxiliary tool in the evaluation of entheseal abnormalities in patients with SpA, especially in patients with advanced age, long symptom duration, and high BMI.